Analysis of Speech Acts in the Short Story "Real Men" By Putu Wijaya - Dian Puspita Sari (Bulletin of Social Studies and Community Development, 2022)
Speech acts are a theory that discusses the meaning of language which is motivated by the relationship between speech and the actions or activities carried out by speakers. The author conducted research on the short story “Laki-laki Sejati” by Putu Wijaya related to locutionary, illocutionary, and perlocutionary speech acts in speeches in events. The research was conducted using a qualitative descriptive method using referential techniques and pragmatic techniques. The aims of this study were (1) to describe the locutionary acts performed on the short story “Laki-laki Sejati” by Putu Wijaya (2) to describe the illocutionary acts performed on the short story “Laki-laki Sejati” by Putu Wijaya (3) to describe the perlocutionary acts on the short story “Laki-laki Sejati” by Putu Wijaya.   Keywords: Speech acts, analysis, pragmatics, heuristics.